Mapping the conceptual structure of green and sustainable human resource management in supply chain management research - Sinyati Ndiango; Leonada Raphael Mwagike; Ismail Abdi Changalima (Discover Sustainability)
Abstract This review aims to map the conceptual structure of green human resource management (GHRM) and sustainable HRM in the context of supply chain management (SCM) research. Through analyzing 127 relevant publications from Scopus (2012 – 2024), the study employs bibliometric analysis tools, including Harzing Publish or Perish, VOSviewer, and the Bibliometrix R package, to assess publication productivity, influential works and keyword co-occurrence analysis. The keyword co-occurrence analysis is used to map the field's conceptual structure. The results reveal a significant growth in research, with an annual growth rate of 32.39%. The recent growth in research productivity has significantly increased since 2019. The study identifies four key themes: 1) the intersection between sustainable HRM and SCM in environmental management and sustainability; 2) the impact of big data analytics and green management on financial and sustainability performance; 3) the role of GHRM in environmental performance and sustainable development; and 4) the influence of green human resources and management on sustainable outcomes. Additionally, the study identified several theories relevant to the research field, with the majority of existing studies utilizing the resource-based view when researching on sustainable and GHRM in the context of SCM. This review offers a comprehensive overview of sustainable and GHRM in the context of SCM, advancing the understanding of sustainability aspects in the research field.